Faulkner at 100 : Retrospect and Prospect - Faulkner, William, 1897-1962; Abadie, Ann J.; Kartiganer, Donald M., 1937- (Book collections on Project MUSE., 2000)
Essays in centennial celebration of William Faulkner and his achievement. With essays and commentaries by Andř Bleikasten, Joseph Blotner, Larry Brown, Thadious M. Davis, Susan V. Donaldson, Doreen Fowler, The Reverend Duncan M. Gray, Jr., Minrose C. Gwin, Robert W. Hamblin, W. Kenneth Holditch, Lothar H̲nnighausen, Richard Howorth, John T. Irwin, Donald M. Kartiganer, Robert C. Khayat, Arthur F. Kinney, Thomas L. McHaney, John T. Matthews, Michael Millgate, David Minter, Richard C. Moreland, Gail Mortimer, Albert Murray, Noel Polk, Carolyn Porter, Hans H. Skei, Judith L. Sensibar.